CYBERBULLYING DALAM FILM SHIRAYUKI HIME SATSUJIN JIKEN - Nuryanti Raihanah; Anisa Arianingsih (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study aims to represent the forms of cyberbullying experienced by Miki Shirono's character and the factors that cause cyberbullying in the Shirayuki Hime Satsujin Jiken film. The method used in this research is descriptive analysis method. The results showed that there were three forms of cyberbullying experienced by Miki Shirono's character such as denigration, outing and trickery, and harassment, then there are two factors that cause cyberbullying, namely excessive internet use and an online forum system that is easy to write using anonymity. This research is expected to make readers understand more wisely and be more careful in using social media as a prevention of cyberbullying.